Distal rectus femoris transfer as part of multilevel surgery in children with spastic diplegia: a randomized clinical trial - Dreher, Thomas; Götze, Marco; Wolf, Sebastian Immanuel; Hagmann, Sébastien; Heitzmann, Daniel; Gantz, Simone; Braatz, Frank (Gait & posture, 2012)
The evidence in support of distal rectus femoris transfer (DRFT) as part of single-event multilevel surgery (SEMLS) is limited due to inconsistent outcome reports and a lack of randomized studies. The purpose of this prospective randomized trial was to establish whether the results of SEMLS without DRFT are similar to those of a conventional approach that includes DRFT in the SEMLS. In all, 32 children with spastic diplegia (GMFCS I-III) and an indication for DRFT were recruited and randomized into a DRFT (15 children) and a NON-DRFT group (17 children) using a minimization method. During SEMLS, bilateral DRFT was performed only in the DRFT group. Three-dimensional gait analysis and clinical examination were performed before and 1year after surgery. In both groups a significant increase in range of motion during swing and knee flexion velocity were found, which was significantly higher in the DRFT group. While peak knee flexion in swing (pKFSw) was preserved in the DRFT group and significantly decreased in the NON-DRFT group, pKFSw timing was significantly earlier in both groups. The clinical relevance of the higher overall benefits in the DRFT group is limited, considering that 33% of patients in this group did not benefit from the procedure. Furthermore, 53% of the NON-DRFT patients did not undergo what proved to be an unnecessary DRFT. Subgroup analysis showed benefits for patients with decreased pKFSw, while those with severe flexed-knee gait (normal or increased pKFSw) did not profit from DRFT. This may explain the inconsistent overall results, and DRFT is therefore not recommended as a “prophylactic” procedure in patients with severe flexed-knee gait.
Gesehen am 29.11.2018